PHARMACOECONOMIC EVALUATION OF ACUTE EXACERBATIONS OF CHRONIC OBSTRUCTIVE PULMONARY DISEASE AT A TERTIARY CARE TEACHING HOSPITAL IN NORTH KARNATAKA, INDIA - S, Rahul; Cr, Abhinand; B, Nikithareddy; K, Jayachandra; P, Lakshmi; H, Doddayya; Ss, Antin (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of the study was to evaluate the burden of cost in patients of acute exacerbations of chronic obstructive lung disease (COPD). Methods: A prospective, observational study was conducted in COPD patients over a period of 6 months in general medicine and pulmonary wards of Navodaya Medical College Hospital and Research Centre, Raichur, Karnataka, India. Direct medical and non-medical cost were included in the burden of cost. From the drug rate manual of hospital, cost for drugs and investigation were calculated. Results: Overall 100 COPD patients were enrolled in which 92 were male and 8 were female with a mean age of 60.33±10.98. The patients participated in this study were stayed in the hospital with mean±standard deviation (SD) value of 9±3. Minimum total direct medical cost was Rs. 1149.00 and maximum was Rs. 13,510.00 with a mean±SD 3297.48±1634.226, in which medicine cost was high (mean 2746.63). Minimum total direct non-medical cost was Rs. 100.00 and maximum was Rs. 3470.00 with a mean±SD 700.7±487.121, in which food expenses was high (mean 549.55). Maximum total direct cost was Rs.16,980.00 and minimum was 1349.00 with a mean± SD 3998.18±1921.47. Direct medical cost contributes 79.56% and direct non-medical cost contribute 20.44% of total direct cost. Conclusion: COPD has a substantial impact on health-care costs particularly for hospitalization. Exacerbation prevention resulting in reduced need for inpatient care could lower costs. The development of pharmacoeconomic is at an infancy stage in India at the moment, despite the rapid growth of clinical research. In a country with scarce resources and an ever-growing population with diverse health-care needs, health economics (Pharmacoeconomic evaluation) plays a pivotal role in determining the delivery of equitable and cost-effective health services.